Effectiveness of Organic Fertilizer Subsidies on the Profitability and Sustainability of Farmers' Savings and Loan Cooperatives - Putu Rani Susanthi; Haldi Jofanda (Perspectives on Advanced New Generations of Global and Local Economic Horizons, 2026)
This study examines the effectiveness of organic fertilizer subsidies and cooperative financial support in shaping the profitability and business sustainability of a farmers' savings and loan cooperative in West Sumatra Province, Indonesia. A quantitative explanatory design was applied to 115 farmer-members who had received the organic fertilizer subsidy through the cooperative's revolving fund scheme. Data were collected using a structured Likert-scale questionnaire and analyzed through validity and reliability testing, classical assumption testing, and multiple linear regression using two structural models. The results show that subsidy effectiveness and cooperative financial support jointly explain 32.6% of the variance in business profitability, while profitability together with the two exogenous variables explains 50.3% of the variance in business sustainability. Both subsidy effectiveness and cooperative financial support have a significant positive effect on profitability (p < 0.001), and profitability, in turn, significantly and positively affects sustainability (p < 0.001), confirming a partial mediation pattern. The findings suggest that organic fertilizer subsidies deliver their strongest welfare impact when channeled through cooperative institutions that simultaneously strengthen farmers' access to affordable credit and savings services. The study contributes to the literature by linking subsidy-policy effectiveness with cooperative financial intermediation and long-term sustainability outcomes, an intersection rarely examined jointly in prior research on Indonesian farmer institutions. Policy implications for subsidy targeting and cooperative capacity-building are discussed.